Epidemiology of patients treated for multiple myeloma using a new algorithm in the French national health insurance database (SNDS): Results from the MYLORD study - Touzeau, Cyrille; Raguideau, Fanny; Denis, Hélène; Lamarsalle, Ludovic; Guilmet, Caroline; Javelot, Matthieu; Pierres, Marie; Perrot, Aurore (PloS one, 2025)
Management of multiple myeloma (MM) has evolved in the last decade, impacting epidemiology and creating the need for a revised algorithm for patient identification in the French National Health Insurance database (SNDS). The objective of the MYLORD study was to provide up-to-date epidemiological indicators for MM using the SNDS. Adults treated for MM between 2014 and 2020 were identified using hospital stays (ICD-10 code C90*) and/or Long-Term Disease status for MM (ICD-10 C90*) and treatment dispensation (MM specific treatments), or lenalidomide or thalidomide with 2 conditions: at least 2 Serum or Urine-Protein Electrophoresis performed within 4 months after the first drug dispensing and no hospital stays for other indications than MM. In 2020 in France, the number of new patients treated for MM was estimated at 5,608, corresponding to a world age-standardized incidence rate (ASIR) of 3.67 (3.55-3.78) per 100,000 patients. The total number of patients treated for MM was estimated at 33,675 corresponding to a world age-standardized prevalence rate (ASPR) of 22.34 (22.06-22.63) per 100,000 patients. The world ASIR slightly increased from 2014 to 2018, then slightly decreased until 2020. There is a regular increase of the ASPR every year in both men and women. The algorithm developed for the MYLORD study considerably improves the identification of patients treated for MM in the SNDS compared to the current French references and allows to generate robust epidemiological indicators. The stable incidence and the increase in prevalence from 2014 to 2020 reflect the improvement in therapeutic management over the years.